2017
DOI: 10.1080/07420528.2017.1279624
|View full text |Cite
|
Sign up to set email alerts
|

Later chronotype is associated with higher hemoglobin A1c in prediabetes patients

Abstract: The circadian system is known to play a role in glucose metabolism. Chronotype reflects the interindividual variability in the phase of entrainment. Those with later chronotype typically prefer later times in the day for different activities such as sleep or meals. Later chronotype has been shown to be associated with metabolic syndrome, increased diabetes risk and poorer glycemic control in type 2 diabetes patients. In addition, "social jetlag", a form of circadian misalignment due to a mismatch between socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 47 publications
(67 reference statements)
3
63
6
1
Order By: Relevance
“…In our study, social jetlag was not related to HbA1c levels (Table 2), as also found in other studies 17, 18 . According to Anothaisintawee et al .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, social jetlag was not related to HbA1c levels (Table 2), as also found in other studies 17, 18 . According to Anothaisintawee et al .…”
Section: Discussionsupporting
confidence: 92%
“…16 , found in patients with type 1 diabetes a positive association between HbA1c and social jetlag (β = 0.012, p < 0.001); HbA1c levels were lower in patients with social jetlag below (≤49 min) versus above (>49 min) the median (7.7% and 8.7%, respectively; p = 0.011). However, in two studies also examining the associations between social jetlag and glycaemic control markers, conducted in pre-diabetic subjects 18 and type 2 diabetes patients 17 , no significant associations were found between circadian misalignment and metabolic control. Two other studies involving the general population 12, 15 revealed that social jetlag is related to a worse metabolic pattern, such as higher fasting plasma insulin, insulin resistance and higher LDL-c and triglyceride levels (p  <  0.05) 12, 15 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to this, a recent study from the UK BioBank comparing definite evening and definite morning types identified an increased likelihood of diabetes in evening orientated individuals with an OR of 1.30 8. Later chronotype is associated with higher HbA1c levels, independent of confounding sleep and clinical variables, in T2DM83 and prediabetes 84. There are conflicting reports of the association of chronotype with glycaemic control in type 1 diabetes: one study reports that more SJL is associated with poorer glycaemic control in adults,85 while in an adolescent cohort chronotype or SJL was not associated with HbA1c levels 86…”
Section: Circadian Rhythms and Healthmentioning
confidence: 88%
“…135 People with prediabetes preferring to consume their main meal in the evening (later chronotype) had higher HbA1c compared to those consuming their main course at lunch time, and thus, had higher risk of developing type 2 diabetes sooner. 136 The American Heart Association in their recent scientific statement concluded that meal frequency and timing may be important parameters in the nutrition management of chronic diseases, leading to healthier lifestyle and reduction in cardiometabolic risk factors. 128 …”
Section: Meal Frequency Meal Timing and Pcosmentioning
confidence: 99%